Dental caries in smokers aged 20–40 years in Mosul City - Ghanim, Layth M.; Gasgoos, Saher Sami (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: Numerous epidemiological studies reported a close relationship between smoking and the occurrence of dental caries. Purpose: To investigate the distribution of tooth decay, lost teeth, and fillings among adults of different smoking habits in Mosul City. Methods: A total of 400 people aged 20–40 years were randomly selected from 30 coffee shops in Mosul City and were divided into 8 groups of 50 participants each, as follows: male non-smokers; male cigarette smokers; male e-cigarette smokers; male hookah smokers; male cigarette + hookah smokers; male e-cigarette + hookah smokers; female hookah smokers; female non-smokers. Participants were examined using the decayed, missing, and filled teeth (DMFT) index. Results: The cigarette group had the greatest average decayed tooth value, followed by the e-cigarette and the hookah group, which had the least. The highest DMFT values were obtained in the cigarette group and the lowest in the hookah group. Missing teeth were highest in the cigarette + hookah group. Hookah-smoking women had significantly higher tooth decay than non-smoking groups. There was no significant difference in missing and filled teeth. Women had more decayed teeth on average than men when smoking hookah. Cigarette-smoking men had the highest percentage who answered “no” to brushing teeth, and the majority of men in each group answered “no” to the use of auxiliary aids. Women in the non-smoking group brushed their teeth on a more regular basis than women in the hookah group, with no difference regarding the usage of auxiliary aids. Conclusion: Smoking increased caries and DMFT values in both men and women.